Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physrevd.91.064001
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of the post-merger gravitational-wave signal from binary neutron stars

Abstract: Extending previous work by a number of authors, we have recently presented a new approach in which the detection of gravitational waves from merging neutron star binaries can be used to determine the equation of state of matter at nuclear density and hence the structure of neutron stars. In particular, after performing a large number of numerical-relativity simulations of binaries with nuclear equations of state, we have found that the post-merger emission is characterized by two distinct and robust spectral f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
451
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(489 citation statements)
references
References 90 publications
(195 reference statements)
33
451
4
1
Order By: Relevance
“…Furthermore, this method could be adapted to constrain or search for other smallamplitude features that might be shared by a population of events, e.g. common parameterized post-Einsteinianlike [43] corrections to the inspiral phase of the mergers, or common equation-of-state-discriminating frequencies excited in hypermassive remnants of binary neutron star mergers [44][45][46][47][48][49][50][51][52][53][54]. In this latter example, one issue in adapting the coherent stacking method would be achieving phase alignment, due to the challenge in accurately calculating the details of the matter dynamics post-merger.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Furthermore, this method could be adapted to constrain or search for other smallamplitude features that might be shared by a population of events, e.g. common parameterized post-Einsteinianlike [43] corrections to the inspiral phase of the mergers, or common equation-of-state-discriminating frequencies excited in hypermassive remnants of binary neutron star mergers [44][45][46][47][48][49][50][51][52][53][54]. In this latter example, one issue in adapting the coherent stacking method would be achieving phase alignment, due to the challenge in accurately calculating the details of the matter dynamics post-merger.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…The approximation in Eq. (60) shows that δf peak =f peak depends only on Q and ρ. From Table I and comparing Figs.…”
Section: B Parameter Estimation For the Peak Frequencymentioning
confidence: 99%
“…(1), which depends on the peak frequency f peak , the quality factor Q, the 22 mode amplitude A 0 , the angle-dependent amplitude factor A r and phase offset ϕ 0 . We estimate the 22 mode frequency (f peak ) using the fit of [12] (see also [11,14,[58][59][60][61] for other fits)…”
Section: B MC Studymentioning
confidence: 99%
“…Besides the prominent peak at f peak , there are several additional peaks in the spectra (see Fig.5). It is suggested that these minor peaks contains rich information of the NS structure [33,[67][68][69].…”
Section: Extraction Of Radius Information By Gw From Merger Remnant Nsmentioning
confidence: 99%
“…Recent numerical relativity simulations of the NS-NS mergers with finite-temperature EOS that can support NS with M ≈ 2M ⊙ [32][33][34] suggest that instead of collapsing to a BH, a massive NS is likely to be formed as the remnant of the merger of canonical mass binary, i.e, if the total binary mass is not extremely high as ≲ 2.8M ⊙ [35] (see also Refs. [36] for pioneering numerical relativity simulations with a simplified EOS).…”
Section: Overview Of Evolution Of Ns-ns and Gw From Itmentioning
confidence: 99%